Crystal structure of poly[(μ 2-1,4-bis(imidazol-1-yl)benzene-k 2 N:N′)(μ 4-biphenyl-3,3′,5,5′-tetracarboxylic-k 4 O,O,O,O)dizinc(II)] dihydrate, C40H28Zn2N8O9 - Yang Xufeng; Liu Debiao; Chen Long; Zhang Zhixue (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C40H28Zn2N8O9, orthorhombic, Fdd2 (no. 43), a = 26.725(3) Å, b = 26.450(2) Å, c = 10.1498(8) Å, V = 7174.7(11) Å3, Z = 8, R gt(F) = 0.0486, wR ref(F 2) = 0.0981, T = 293(2) K.